Developments in the field of allergy in 2013 through the eyes of Clinical and Experimental Allergy. Issue 12 (December 2014) - Blankestijn, M. A.; Boyle, R. J.; Gore, R.; Hawrylowicz, C.; Jarvis, D.; Knulst, A. C.; Wardlaw, A. J.
Summary 2013 was another exciting year for allergy in general and Clinical and Experimental Allergy in particular. In the field of asthma and rhinitis, there continued to be a focus on heterogeneity and phenotypes with increasing use of biostatistical techniques to determine clusters of similar populations. Obesity‐ and aspirin‐associated disease are intriguing associations with asthma which were explored in a number of papers. We published a number of excellent papers on mechanisms of airway inflammation and how this relates to physiology, pathology, genetics and biomarkers in both human and experimental model systems. In terms of mechanisms, there is less on individual cell types in allergic disease at the moment, but the immunology of allergic disease continued to fascinate our authors. Another area that was popular both in the mechanisms and in the epidemiology sections was early life events and how these lead to allergic disease, with an increasing focus on the role of the microbiome and how this influences immune tolerance. In the clinical allergy section, oral immunotherapy for food allergy is clearly a major topic of interest at the moment as was in vitro testing to distinguish between sensitization and allergic disease. There was less on inhalant allergy this year, but a good representation from the drug allergy community including some interesting work on non‐IgE‐mediated mechanisms. In the allergen section, important new allergens continue to be discovered, but the major focus as in the last couple of years was on working out how component‐resolved approaches can improve diagnosis and management of food and venom allergy.